THE EFFECT OF RETURN ON ASSET, RETURN ON EQUITY, AND EARNING PER SHARE IN THE STOCK PRICES OF TOURISM AND HOSPITALITY COMPANIES LISTED IN THE INDONESIA STOCK EXCHANGE 2013-2017 - Ditarosa Taurista Jatmika; Agus Sukoco; Joko Suyono; Damarsari Ratnasahara Elisabeth (Journal of World Conference (JWC), 2019)
This research aims to analyze the effect of Return On Assets, Return On Equity and Earning Per Share on companies stock prices. The research method used is multiple linear regression analysis. This study used secondary data from tourism and hospitality sub-sector companies listed in the Indonesia Stock Exchange. The number of research samples is 13 tourism and hospitality companies that report financial reports regularly and have been audited with the period 2013-2017. The results Return On Asset has a partially effect in stock prices but not significant, Return On Equity has a partially effect in stock prices but not significant, Earnings Per Share has a partially influence in stock prices but significant, Return On Assets, Return On Equity and Earning Per Share has a simultanly influence in the stock prices.